Melatonin Alleviates Antimony Toxicity by Regulating the Antioxidant Response and Reducing Antimony Accumulation in Oryza sativa L. - Yutan Chu; Qiongli Bao; Yan Li; Hongyu Sun; Zewei Liu; Jiahao Shi; Yizong Huang (MDPI AG, 2023)
Antimony (Sb) is a hazardous metal element that is potentially toxic and carcinogenic. Melatonin (MT) is an indole compound with antioxidant properties that plays an essential role in plant growth and alleviates heavy metal stresses. Nevertheless, little is known about the effects and mechanisms of exogenous MT action on rice under Sb stress. The aim of this experiment was to explore the mechanism of MT reducing Sb toxicity in rice via hydroponics. The results showed that Sb stress significantly inhibited the growth of rice, including biomass, root parameters, and root viability. Exogenous MT obviously alleviated the inhibition of Sb stress on seedling growth and increased biomass, root parameters, and root viability by 15-55%. MT significantly reduced the total Sb content in rice and the subcellular Sb contents in roots by nearly 20-40% and 12.3-54.2% under Sb stress, respectively. MT significantly decreased the contents of malondialdehyde (MDA, by nearly 50%), ROS (H2O2 and O2·−, by nearly 20-30%), and RNS (NO and ONOO−) in roots under Sb stress, thus reducing oxidative stress and cell membrane damage. Furthermore, MT reversed Sb-induced phytotoxicity by increasing the activities of antioxidant enzymes (SOD, POD, CAT, and APX) by nearly 15% to 50% and by regulating the AsA-GSH cycle. In conclusion, this study demonstrates the potential of MT to maintain redox homeostasis and reduce Sb toxicity in rice cells, decreasing the content of Sb in rice and thereby alleviating the inhibition of Sb on rice growth. The results provided a feasible strategy for mitigating Sb toxicity in rice.